ANALISIS INTENSI MUZAKKÎ DALAM MEMBAYAR ZAKAT PROFESI - Huda, Nurul; Ghofur, Abdul (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
The aims of this research is to determine the influence of attitude, subjective norm, behavioral control, muzakkî income, muzakkî education, and muzakkî knowledge to the muzakkî intention of paying profession zakâh. The method of the research is a quantitative method while data analysis  techniques use multiple regression analysis. Number of samples analyzed are 150 respondents drawn at random from all areas of Jakarta. Based onmultiple regression analysis, it can be seen that the variables together attitudes, subjective norms, behavior control, income, education, and knowledge has significant influence on the variable of muzakkî intention.DOI: http://dx.doi.org/10.15408/aiq.v4i2.2471